Cognitive-behavioral teletherapy for children and adolescents with mental disorders and their families during the COVID-19 pandemic: a survey on acceptance and satisfaction - Lea Meininger; Julia Adam; Elena von Wirth; Paula Viefhaus; Katrin Woitecki; Daniel Walter; Manfred Döpfner (BMC, 2022)
Abstract Background The COVID-19 pandemic is challenging for health care systems around the world. Teletherapy (psychotherapy conducted via videoconference) for children and adolescents offers a promising opportunity not only to provide treatment during social distancing restrictions but also to reduce treatment barriers that might prevent families from seeking care independent of the pandemic. Therefore, it is highly important to examine the implementation and especially the acceptance of and satisfaction with teletherapy. Methods Therapists of 561 patients and parents of 227 patients (total 643 patients) aged 3-20 years treated at a university outpatient unit rated their experiences with teletherapy. Results Following the outbreak of COVID-19, 73% of the patients switched from face-to-face treatment to teletherapy. Both therapists and parents were mainly satisfied with teletherapy and did not report negative impacts on treatment satisfaction or the therapeutic relationship. Stress from COVID-19, age, gender, duration of treatment, psychosocial functioning, and psychopathology were associated with satisfaction, but correlations were low. Sixty-six percent of parents and 53% of therapists intended to use teletherapy in the future. Conclusions Teletherapy during the COVID-19 pandemic was well accepted by both parents and therapists. Certain patient characteristics were related to satisfaction. Trial registration The study was retrospectively registered in the German Clinical Trials Register (DRKS00028639).